Effect of weathering and thickness on the superficial microhardness of acrylic resin and ocular button - Rocha Fernandes, Aline Ursula; Goiato, Marcelo Coelho [UNESP]; Santos, Daniela Micheline dos [UNESP] (Elsevier B.V., 2009)
Purpose: This study evaluated the effects of weathering (1008 h) and thickness (1 and 3.5 mm) on the superficial microhardness of the ocular button, using five colorless acrylic resins, and colorless buttons specific for ocular prosthesis.Materials and methods: One-hundred-and-twenty specimens were made and distributed allocated to 12 groups. Microhardness analysis was carried out with a microdurometer (Shimadzu, Japan) before and after weathering for 1008 h. Data were then analyzed statistically by ANOVA and the Tukey Test at 1% significance.Results: The data demonstrated that the ocular button and the QC 20 resin presented, respectively, the highest (22.9) and lowest (18.31) values of surface microhardness (Knoop), independently of the variable evaluated.Conclusion: Thickness did not influence the property studied, and the specimens presented higher mean values of superficial microhardness after weathering for 1008 h. (C) 2009 British Contact Lens Association. Published by Elsevier Ltd. All rights reserved.
Keywords: Aesthetic; Ocular prosthesis; Hardness; Acrylic resin